Causal and Associational Language in Observational Health Research: A Systematic Evaluation. Issue 12 (4th August 2022) - Haber, Noah A; Wieten, Sarah E; Rohrer, Julia M; Arah, Onyebuchi A; Tennant, Peter W G; Stuart, Elizabeth A; Murray, Eleanor J; Pilleron, Sophie; Lam, Sze Tung; Riederer, Emily; Howcutt, Sarah Jane; Simmons, Alison E; et al.
Abstract: We estimated the degree to which language used in the high-profile medical/public health/epidemiology literature implied causality using language linking exposures to outcomes and action recommendations; examined disconnects between language and recommendations; identified the most common linking phrases; and estimated how strongly linking phrases imply causality. We searched for and screened 1, 170 articles from 18 high-profile journals (65 per journal) published from 2010–2019. Based on written framing and systematic guidance, 3 reviewers rated the degree of causality implied in abstracts and full text for exposure/outcome linking language and action recommendations. Reviewers rated the causal implication of exposure/outcome linking language as none (no causal implication) in 13.8%, weak in 34.2%, moderate in 33.2%, and strong in 18.7% of abstracts. The implied causality of action recommendations was higher than the implied causality of linking sentences for 44.5% or commensurate for 40.3% of articles. The most common linking word in abstracts was "associate" (45.7%). Reviewers' ratings of linking word roots were highly heterogeneous; over half of reviewers rated "association" as having at least some causal implication. This research undercuts the assumption that avoiding "causal" words leads to clarity of interpretation in medical research.